IDDF2022-ABS-0182 Comparing the diagnostic accuracy of renal resistive index and urine neutrophil gelatinase-associated lipocalin (NGAL) in differentiating type of acute kidney injury in decompensated cirrhosis. (2nd September 2022) - George, Roshan; Kumar, Ajay; Sonika, Ujjwal
Abstract : Background: Acute kidney injury (AKI) in patients with decompensated cirrhosis is associated with increased mortality. The three common types of AKI are pre-renal azotemia (PRA), acute tubular necrosis (ATN) and hepatorenal syndrome (HRS). It is important to determine type of AKI, since prognosis and treatment depend on it. Urine Neutrophil Gelatinase-associated Lipocalin (NGAL) his a useful biomarker for differentiating types of AKI. Renal resistive index (RRI) can be computed easily using ultrasound. However, few studies have evaluated the diagnostic accuracy of RRI in differentiating types of AKI in cirrhotics. Methods: Consecutive patients with decompensated cirrhosis admitted with AKI stage ≥ IB (Creatinine >1.5mg/dl) or who develop AKI stage ≥ IB during hospitalisation were included. AKI was defined as per ICA-AKI (International Club of Ascites-AKI) criteria. RRI and urine NGAL was measured on day of AKI diagnosis (Day 0) and repeated 48 hrs after albumin administration (Day 3). The study compared the diagnostic accuracy of RRI and urine NGAL, using clinical adjudication as the gold standard for determining type of AKI. Results: The study included 86 decompensated cirrhotics with AKI. Mean age of patients was 48.73±12.53 years . 86 % were males. PRA(54.6 % ) was the most common cause of AKI. For differentiating ATN and non-ATN AKI on day 0, urine NGAL had superior diagnostic accuracy vs RRI (AUROC-0.97 (95% CI, 0.95 - 1.0) vs 0.68 (95% CI, 0.55 - 0.80 ); on day 3, urine NGAL was superior to RRI (0.97 (95% CI, 0.94 - 1.0) vs 0.73 (95% CI, 0.63 - 0.84) . For differentiating HRS-AKI and non-HRS-AKI, on day 0, AUROC for diagnostic accuracy of RRI was similar to NGAL (0.80 (95% CI, 0.69 - 0.91) vs 0.72 (95% CI, 0.61 - 0.82 ); On day 3, diagnostic accuracy of RRI was similar to NGAL (0.67 (95% CI, 0.54 - 0.80) vs 0.73 (95% CI, 0.62 - 0.83) ). 28 -day mortality was high in the study cohort (45.3 % ). Conclusions: Urine NGAL is superior to RRI in differentiating ATN vs non-ATN AKI. RRI is a potentially useful, easily available modality to differentiate between HRS and non-HRS-AKI in decompensated cirrhosis patients .